Description of The Level Of Knowledge Dietary Patterns for Diabetes Mellitus Among The Elderly at The Brati Community Health Center - Charisma Alzura; Adisty Rose Artistin (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
As per the data from World Population Projection, there are currently 901 million individuals who are over 60 years of age. It is anticipated that this number will rise by approximately 56%, from 901 million to 1.4 billion. Hyperglycemia, or elevated blood sugar levels, is a hallmark of diabetes mellitus (DM), a chronic metabolic disease brought on by an imbalance between the supply and demand of insulin (David et al., 2018). Under the heading